Inhibition of Aldehyde Dehydrogenase‐Activity Expands Multipotent Myeloid Progenitor Cells with Vascular Regenerative Function. (12th February 2018) - Cooper, Tyler T.; Sherman, Stephen E.; Kuljanin, Miljan; Bell, Gillian I.; Lajoie, Gilles A.; Hess, David A.
Abstract: Blood‐derived progenitor cell transplantation holds potential for the treatment of severe vascular diseases. Human umbilical cord blood (UCB)‐derived hematopoietic progenitor cells purified using high aldehyde dehydrogenase (ALDH hi ) activity demonstrate pro‐angiogenic functions following intramuscular (i.m.) transplantation into immunodeficient mice with hind‐limb ischemia. Unfortunately, UCB ALDH hi cells are rare and prolonged ex vivo expansion leads to loss of high ALDH‐activity and diminished vascular regenerative function. ALDH‐activity generates retinoic acid, a potent driver of hematopoietic differentiation, creating a paradoxical challenge to expand UCB ALDH hi cells while limiting differentiation and retaining pro‐angiogenic functions. We investigated whether inhibition of ALDH‐activity during ex vivo expansion of UCB ALDH hi cells would prevent differentiation and expand progeny that retained pro‐angiogenic functions after transplantation into non‐obese diabetic/severe combined immunodeficient mice with femoral artery ligation‐induced unilateral hind‐limb ischemia. Human UCB ALDH hi cells were cultured under serum‐free conditions for 9 days, with or without the reversible ALDH‐inhibitor, diethylaminobenzaldehyde (DEAB). Although total cell numbers were increased >70‐fold, the frequency of cells that retained ALDH hi /CD34+ phenotype was significantly diminished under basal conditions. In contrast, DEAB‐inhibition increased total ALDH hi /CD34+ cell number by ≥ 10‐fold, reduced differentiation marker (CD38) expression, and enhanced the retention of multipotent colony‐forming cells in vitro. Proteomic analysis revealed that DEAB‐treated cells upregulated anti‐apoptotic protein expression and diminished production of proteins implicated with megakaryocyte differentiation. The i.m. transplantation of DEAB‐treated cells into mice with hind‐limb ischemia stimulated endothelial cell proliferation and augmented recovery of hind‐limb perfusion. DEAB‐inhibition of ALDH‐activity delayed hematopoietic differentiation and expanded multipotent myeloid cells that accelerated vascular regeneration following i.m. transplantation in vivo. Stem Cells 2018;36:723–736 Abstract : Inhibition of aldehyde dehydrogenase activity limits hematopoietic progenitor cell differentiation and enhances the expansion of UCB ALDH hi progeny with vascular regenerative function.